4D printing of light activated shape memory polymers with organic dyes - Gastaldi, Matteo; Spiegel, Christoph A.; Vázquez-Martel, Clara; Barolo, Claudia; Roppolo, Ignazio; Blasco, Eva (Molecular systems design & engineering, 2023)
Light based 3D printing technologies, such as digital light processing (DLP), allow for the additive manufacturing of complex 3D objects at fast speeds and with high resolution. Typical printable formulations for DLP consist of (a mixture of) monomer(s), a photoinitiator and very often, an organic dye absorbing at the printing wavelength in order to improve the resolution. Herein, we exploit the use of push-pull azobenzene (azo) dyes to not only enhance printing resolution but also to enable light response (fourth-dimension) of printed shape memory polymers (SMPs) employing DLP without the necessity of adding inorganic additives. In particular, a library of azo-dyes with different substituents in ortho-position have been synthesized and added as active dyes in the printing formulation. The light activated shape memory effect is demonstrated for all the printed structures including the dyes. Among all of them, the structures containing chlorine-substituted azo dyes show the best performance. Importantly, the desired effect is achieved with only 0.1 wt% of dye in the formulation. Furthermore, we demonstrate the potential of using visible light as stimulus for spatially resolved activation of complex structures on demand.